Ertugliflozin to reduce arrhythmic burden in ICD/CRT patients (ERASe-trial). a phase III study. (14th October 2021) - Von Lewinski, D; Tripolt, N; Sourij, H; Oulhaj, A; Gwechenberger, M; Martinek, M; Nuernberg, M; Roithinger, F.X; Steinwender, C; Stuehlinger, M; Rohrer, U; Manninger-Wuenscher, M; et al.
Abstract: Background and aim: Sodium glucose cotransporter 2 (SGLT2) have proven profound positive effects in heart failure with reduced ejection fraction (HFrEF). These effects are independent from the presence of diabetes. Since SGLT2 receptors are not expressed in human myocardium, these cardioprotective effects be indirect or pleiotropic. Besides metabolic effects anti-inflammatory anti-fibrotic properties are discussed. Despite a strong correlation of ventricular arrhythmias with HFrEF, the impact of ertugliflozin on the arrhythmic burden has not been investigated, yet. Therefore, the Ertugliflozin to Reduce Arrhythmic burden in ICD/CRT patientS (ERASe) trial was designed to investigate the efficacy and safety of ertugliflozin in diabetic and non-diabetic HFrEF patients. Methods: Methods: Within a multicentre, national, randomized, double-blind, placebo-controlled, phase 3b trial we aim to enrol a total of 402 patients across Austria. Patients with HFrEF or HFmrEF and ICD±CRT therapy >3 months and previous ventricular tachycardia (at least 10 documented non-sustained VT episodes within the last 12 months) are randomized in a 1:1 ratio to ertugliflozin (5mg once daily orally administered) or matching placebo. The primary endpoint of the ERASe trial is to investigate the impact of Ertugliflozin on total burden of ventricular arrhythmias. Further objectives will be the number of therapeutic interventions of implanted devices, atrial fibrillation, heart failure biomarker and changes in physical function quality of life, stress and anxiety. Conclusion: The ERASe trial will be the first trial to test ertugliflozin in heart failure patients with non-preserved ejection fraction and ongoing ICD/CRT therapy regardless of their diabetic status. The ERASe trial may therefore extend the concept of SGLT2 inhibition to improve cardiac reverse remodelling, including reduced arrhythmic burden. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): unrestricted grant of MSD